Chemotherapy for small cell lung cancer: a comprehensive review - Syed Mustafa Karim; Jamal Zekri (Oncology Reviews, 2012)
Combination chemotherapy is the current strategy of choice for treatment of small cell lung cancer (SCLC). Platinum containing combination regimens are superior to non-platinum regimens in limited stage- SCLC and possibly also in extensive stage-SCLC as first and second-line treatments. The addition of ifosfamide to platinum containing regimens may improve the outcome but at the price of increased toxicity. Suboptimal doses of chemotherapy result in inferior survival. Early intensified, accelerated and high-dose chemotherapy gave conflicting results and is not considered a standard option outside of clinical trials. A number of newer agents have provided promising results when used in combination regimens, for example, gemcitabine, irinotecan and topotecan. However, more studies are required to appropriately evaluate them. There is a definitive role for radiotherapy in LD-SCLC. However, timing and schedule are subject to further research. Novel approaches are currently being investigated in the hope of improving outcome.